Transformation of tetrachloromethane to dichloromethane and carbon dioxide by Acetobacterium woodii - Egli, Christine; Tschan, Thomas; Scholtz, Rudolf; Cook, Alasdair M.; Leisinger, Thomas (My University, 1988)
Five anaerobic bacteria were tested for their abilities to transform tetrachloromethane so that information about enzymes involved in reductive dehalogenations of polychloromethanes could be obtained. Cultures of the sulfate reducer Desulfobacterium autotrophicum transformed some 80 microM tetrachloromethane to trichloromethane and a small amount of dichloromethane in 18 days under conditions of heterotrophic growth. The acetogens Acetobacterium woodii and Clostridium thermoaceticum in fructose-salts and glucose-salts media, respectively, degraded some 80 microM tetrachloromethane completely within 3 days. Trichloromethane accumulated as a transient intermediate, but the only chlorinated methanes recovered at the end of the incubation were 8 microM dichloromethane and traces of chloromethane. Desulfobacter hydrogenophilus and an autotrophic, nitrate-reducing bacterium were unable to transform tetrachloromethane. Reduction of chlorinated methanes was thus observed only in the organisms with the acetyl-coenzyme A pathway. Experiments with [14C]tetrachloromethane were done to determine the fate of this compound in the acetogen A. woodii. Radioactivity in an 11-day heterotrophic culture was largely (67%) recovered in CO2, acetate, pyruvate, and cell material. In experiments with cell suspensions to which [14C]tetrachloromethane was added, 14CO2 appeared within 20 s as the major transformation product. A. woodii thus catalyzes reductive dechlorinations and transforms tetrachloromethane to CO2 by a series of unknown reactions.
Keywords: 570